A Monitoring System of Ankle Rehabilitation For Paralyzed Patients Using Android Aplication - Hanum Arrosida; Asih Setiarini; Basuki Winarno; Albert Sudaryanto (Kinetik: Game Technology, Information System, Computer Network, Computing, Electronics, and Control, 2019)
A Monitoring system of ankle rehabilitation for paralyzed patients was successfully designed. The monitoring application on Android smartphone was made app inventor. This application uses bluetooth HC-05 as a data transmission between the ankle therapy aids and smartphone Android. A MPX5050DP sensor is used to determine the muscle condition of the paraplegic to measure the muscle strength scale and control the motor dc speed of ankle rehabilitation hardware. The virtual keys on the application are five instructions of therapeutic movement such as, dorsiflexion (200), plantarflection (450), eversion (100), inversion (100) and patterned of movement. The access time to operate the ankle rehabilitation hardware is 0.8 seconds. This application includes an alarm and a database that can be used as a monitoring system. An alarm menu serves as a reminder for patients to take therapy and database to store data readings of sensors that converted into scale and muscle pressure. A MPX55050DP sensor output is displayed on smartphone application, stored in database and the therapy results are reserved to document format. The capacity of the database corresponds to the memory on the smartphone. Based on the measurement results, the ankle therapy application on android smartphone can control the system movement of ankle therapy aids and as a monitoring system of therapy results for paralyzed patients and make easily in analyzing the condition of leg muscle strength.